Rhythmic Effects of Syntax Processing in Music and Language - Jung, Harim; Sontag, Samuel; Park, YeBin S.; Loui, Psyche (Frontiers in Psychology, 2015)
Music and language are human cognitive and neural functions that share many structural similarities. Past theories posit a sharing of neural resources between syntax processing in music and language (Patel, 2003), and a dynamic attention network that governs general temporal processing (Large & Jones, 1999). Both make predictions about music and language processing over time. Experiment 1 of this study investigates the relationship between rhythmic expectancy and musical and linguistic syntax in a reading time paradigm. Stimuli (adapted from Slevc et al., 2009) were sentences broken down into segments; each sentence segment was paired with a musical chord and presented at a fixed inter-onset interval. Linguistic syntax violations appeared in a garden-path design. During the critical region of the garden-path sentence, i.e. the particular segment in which the syntactic unexpectedness was processed, expectancy violations for language, music, and rhythm were each independently manipulated: musical expectation was manipulated by presenting out-of-key chords and rhythmic expectancy was manipulated by perturbing the fixed inter-onset interval such that the sentence segments and musical chords appeared either early or late. Reading times were recorded for each sentence segment and compared for linguistic, musical, and rhythmic expectancy. Results showed main effects of rhythmic expectancy and linguistic syntax expectancy on reading time. There was also an effect of rhythm on the interaction between musical and linguistic syntax: effects of violations in musical and linguistic syntax showed significant interaction only during rhythmically expected trials. To test the effects of our experimental design on rhythmic and linguistic expectancies, independently of musical syntax, Experiment 2 used the same experimental paradigm, but the musical factor was eliminated – linguistic stimuli were simply presented silently, and rhythmic expectancy was manipulated at the critical region. Experiment 2 replicated effects of rhythm and language, without an interaction. Together, results suggest that the interaction of music and language syntax processing depends on rhythmic expectancy, and support a merging of theories of music and language syntax processing with dynamic models of attentional entrainment.